A new cryptic species of Oreobates (Anura: Craugastoridae) from the seasonally dry tropical forest of central Brazil - Vaz-Silva, Wilian; Maciel, Natan Medeiros; de Andrade, Sheila Pereira; Amaro, Renata Cecília (Zootaxa, 2018)
A new species of Oreobates Jiménez de la Espada, 1872 is described from the seasonally dry tropical forest associated to rocky outcrops of the northeastern Goiás State, Central Brazil. Oreobates antrum sp. nov. is diagnosable by the combination of morphological characters (e.g. small size, dorsal and ventral skin texture smooth to finely shagreened, and broadly enlarged truncate discs on Fingers III and IV), call attributes (composed of a single note and no harmonics with dominant frequency ranged 2070 Hz to 3273 Hz), and supported by molecular evidence (phylogenetic position and genetic divergence) with high degree of differentiation among other Oreobates species (divergences of 4.0–20.6% for 12S, 7.0–14% for 16S, 0.7–4.0% for RAG-1, and 1.1–8.0% for TYR). The new species was recovered as the sister of Oreobates remotus.